Introgression of cultivated sunflower in exotic Helianthus petiolaris populations - Gutierrez, Agustina (2012)
Cultivated sunflower Helianthus annuus and the wild exotic H. petiolaris are sympatric species in an extensive region of central Argentina. Both species are sexually compatible, they overlap their flowering time and share pollinators in the region. Although there are important barriers to introgression between them, interspecific hybrids are occasionally found in contact zones. We present evidences of crop introgression in H. petiolaris populations under natural conditions and controlled and semi-controlled crosses in the experimental field using morphological traits. If crop genes persist in subsequent generations after hybridization, it could then be possible to find crop morphological traits and molecular markers in hybrid offsprings. Plants of H. petiolaris, sunflower and plants of intermediate morphology (IMP) were characterized in their natural habitats, and progenies of IMPs were grown in a common garden and compared to progenies of interspecific hybrids obtained by open pollination and backcrosses to H. petiolaris. Variability of IMPs in the wild was comparable to variability under experimental conditions, thus confirming introgression from sunflower in H. petiolaris populations. Molecular markers confirmed introgression. This has implications on the usage of herbicide tolerant sunflower varieties and the likely release of genetic modified varieties in agro-ecological regions invaded by H. petiolaris populations.